Understanding and using english grammar - Azar, Betty Schrampfer (Thanh niên, 2000)
For nearly forty years, Understanding and Using English Grammar has been the go-to grammar resource for students and teachers alike. Its time-tested approach blends direct grammar instruction with carefully sequenced practice to develop all language skills.